(untitled) (Biodiversitas Journal of Biological Diversity, 2015)
Tapilatu RF, Ballamu F. 2015. Nest temperatures of the Piai and Sayang Islands green turtle (Chelonia mydas) rookeries, Raja Ampat Papua, Indonesia: Implications for hatchling sex ratios. Biodiversitas 16: 102-107. Sex determination and hatching success in sea turtles is temperature dependent. Warmer sand temperatures may skew sea turtle population sex ratios towards predominantly females and high sand temperatures may also decrease hatching success. Therefore, understanding nest temperatures is important for conservation programs, including the evaluation of the potential impact of global climate change. Nest temperatures were monitored during the 2013 nesting season of the green sea turtle, Chelonia mydas, at Piai and Sayang Islands, Raja Ampat, West Papua, Indonesia. Nest temperatures increased from 29oC early in the incubation to 34-36oC in the middle, before decreasing again. Monitored nest temperatures were similar across all beaches. Nest temperatures increased 2-4oC during the middle third of incubation due to metabolic heating. Hatchling sex ratio inferred from nest temperature profiles indicated a strong female bias. This finding is consistent with the relatively warm thermal profiles of the majority of the nesting beaches. This also included some extremely warm nest temperatures that were associated with lower hatching success. Information from this study provides a foundation for developing conservation strategies for enhancing hatchling production with optimal sex ratios at the most important nesting beaches for the western Pacific green sea turtle. This study is the first comprehensive assessment of sex ratios for green sea turtles in Raja Ampat and represents the initiation of a long-term database that can be used at a local level to develop strategies that could potentially offset the impact of long-term climate change on the western Pacific green sea turtle.